Educating Students to Consistency via Argumentation - Montanari, Elisabetta (Informal Logic, 2019)
In this paper, the role played in learning to argue by an essential and yet under-researched epistemic and argumentative norm is discussed, namely, the consistency requirement. An argumentative intervention is presented, that is designed to enhance the understanding of this norm among high school students, to enable them to recognize contradictions in the process of argumentation and to familiarize them with the argumentative strategies related to the reductio ad absurdum. There follows a description of how the designed intervention was implemented in two Italian high schools, which served as an exploratory case study, and the results obtained are discussed.